PRONOMINA BAHASA MELAYU RIAU ISOLEK SERAPUNG KABUPATEN PELALAWAN - Roza, Widia; Sinaga, Mangatur; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the use of pronouns Riau Malay language isolate Serapung. The data in this research are informant's speech in the form of pronouns persona, pronoun pointer, and pronoun of the questioner in Riau Malay isolat Serapung. This research type is qualitative research with descriptive method. This research was conducted using interview technique, fishing technique, recording technique, and recording technique. Data analysis technique which writer traskip pronomina data which have been obtained from interview and recording technique into writing form, grouping data based on problem formulation, data analysis based on symptom concluding result of research indicate that pronounce of Riau Malay language isolasi Serapung consist of (1) pronounce persona , (2) pronoun pointers, and (3) pronouns of the questioner. The first person's pronomina, second person pronoun, and third person pronoun are divided into singular and plural forms. The form of pronouns persona Malay language Riau isolek Serapung is saye, me, us, kite, crew, you, dikau, tengku, said, syarifah, name, mike, die, he, and people. Pronoun precisely consists of a general pronoun, a place pronoun, and a pointing pronoun. The form of pronoun pointer is ike, that, sike, sane, situ, gini, and so. The pronoun form of the questioner is. siape, ape, berape, ngape, mane kind.Keywords: Pronouns, pronouns persona, pronoun pointer, pronouns questioner